Association between dairy products intake and frailty transitions in older adults: The InCHIANTI cohort study - Nicole Hidalgo-Liberona; Tomás Meroño; Raul Zamora-Ros; Caterina Trevisan; Massimiliano Fedecostante; Stefania Bandinelli; Luigi Ferrucci; Antonio Cherubini; Cristina Andres-Lacueva (The Journal of Nutrition, Health and Aging)
Objective: To evaluate the association between dairy products consumption and the probability of frailty transitions in community-dwelling older adults. Design: Longitudinal study. Setting and participants: We included 863 community-dwelling participants ≥65 years from the Chianti region in Italy. Mesurements: Habitual dietary intake of dairy products (i.e., milk, yogurt, and cheese) was assessed in daily servings using a validated food frequency questionnaire (FFQ) at baseline, 3-, 6-, and 9-years of follow-up. Frailty status at each visit was defined using the Fried criteria, and the probability of transitions between different frailty status and death was assessed through multistate models. The associations between dairy product intakes and frailty transitions during the 9-year period were expressed as hazard ratios (HRs) derived from proportional intensity models. Results: The mean age at baseline was 74 ± 7 years and 46% of the participants were male. There were no statistically significant associations between the consumption of total, fermented, or non-fermented dairy products and the probabilities of transition from robust or from pre-frail to any of the other frailty conditions or to death. Conversely, a direct association between the consumption of fermented dairy products and the probability of transition from frail to pre-frail was observed in a model adjusted for age, sex, and energy intake (HRper serving/day = 1.90, 95%CI 1.12−3.22). This association was primarily related to yogurt consumption (HRper serving/day = 4.07, 95%CI 1.38−12.02), as the association with cheese consumption was not significant (HRper serving/day = 1.57, 95%CI 0.91−2.71). In the fully adjusted model, only the association between yogurt consumption and frail to pre-frail transition remained statistically significant (HRper serving/day = 3.68, 95%CI 1.10−12.31). Conclusion: Dairy products, such as milk, yogurt, and cheese, are unlikely to play a predominant role in frailty development in an Italian community-dwelling older population. However, it is advisable to maintain a moderate consumption of dairy products, especially fermented ones, as part of a well-balanced diet to promote healthy aging.